Impact of Human Capital Development Initiatives on Well-Being of employees with chronic illness (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper is a tribute to the unsung warriors  of organisations who brave the daily challenges  of chronic illness, cloaked in a conspiracy of  silence. The study attempts to present the role  of human capital development initiatives in  enhancing the psychological well-being of an  overlooked section of diversity – Employees  with chronic illness. According to the United Nations, even though  employment “Provides many opportunities  for social participation, from economic  independence, to family formation, to a sense of  contributing to the national economy” (United  Nations 2007, p. 85), worldwide, 80 to 90%  of working-age persons with disabilities are  unemployed. (United Nations 2010). Chronic Illness literature (Beatty & Joffe,  2006) presents the fact that employees suffering  from disability caused by chronic illness are  often overlooked in the narratives of positive  organisational support and human capital  development. One of the main reasons being  that disability caused by chronic illness doesn’t  follow a predictable path and thus poses a  challenge to policy framing. The illnesses range  from mild to severe, low interference to high  interference, episodic to ongoing, and above  all visible to invisible. Chronic diseases are  responsible for contributing the largest share to  the overall mortality in the developing countries,  except for Sub-Saharan Africa (Suhrcke, Nugent,  Stuckler, &; Rocco, 2006). Most commonly occurring illnesses include  cardiovascular diseases, cancers, diabetes,  and chronic respiratory diseases (World  Health Organization (WHO), 2018). The  other common chronic diseases could be  musculoskeletal disorders, multiple sclerosis,  epilepsy, migraines and many more.
Keywords: Organization; cancers; challenges